Dosis Optimum Larutan Kapur untuk Netralisasi pH Air Limbah Penambangan Batubara - Ahmad Faisal; Syarifudin A. (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2014)
Abstrak: Optimum Dose of Hydrated Lime for pH Neutralizing in Coal Mine Waste-water. Coal mines release chemicals such as pyrite (Fe2S), produce acid waste water (H2SO4). This research aims to know the optimum dose of hydrated lime to neutralize the pH of coal mining wastewater. This research was experimental study with pretest-postest with control group design, measured pH before and after treatment. Coal mines wastewater was sampled with composite sampling method. The result showed that the average of waste-water’s pH before added 2% hydrated lime were 4,9, while wastewater added by variated dose of hydrated lime, the pH changed. Added 1, 3, 5, 7 and 9 ml hydrated lime, the pH particularly to be 5,3, 7,1, 8,2, 9,7 and 10,5. Statistical test using One Way Anova showed the p value = 0,000, ore less than α = 0,05. There was the difference significantly between pH’s average of coal mine wastewater at variation in dose of 2% hydrated lime. Test of Linier regression found equation; y = 4,906 + 0,649x with correlation value (R) = 0,982. Optimum dose of 2% hydrated lime for pH neutralizing 1 litre of coal mine wastewater was 3,23, pH=7.Keyword: Air limbah batubara; larutan kapur; pH